Discovery of anti-TB agents that target the cell-division protein FtsZ. (August 2010) - Kumar, Kunal; Awasthi, Divya; Berger, William T; Tonge, Peter J; Slayden, Richard A; Ojima, Iwao
The emergence of multidrug-resistant Mycobacterium tuberculosis strains has made many of the currently available anti-tuberculosis (TB) drugs ineffective. Accordingly, there is a pressing need to identify new drug targets. Filamentous temperature-sensitive protein Z (FtsZ), a bacterial tubulin homologue, is an essential cell-division protein that polymerizes in a GTP-dependent manner, forming a highly dynamic cytokinetic ring, designated as the Z ring, at the septum site. Other cell-division proteins are recruited to the Z ring and, upon resolution of the septum, two daughter cells are produced. Since inactivation of FtsZ or alteration of FtsZ assembly results in the inhibition of Z-ring and septum formation, FtsZ is a very promising target for novel antimicrobial drug development. This review describes the function and dynamic behaviors of FtsZ and the recent development of FtsZ inhibitors as potential anti-TB agents.